Rooting stem cuttings of shantung maple (Acer truncatum), mound layering shantung and caddo sugar maples (Acer saccharum), and using Eastern redcedar (Juniperus virginiana) as a substrate component in stem cutting propagation - Brock, Justin Alan (Kansas State University, 2014)
Heat and drought tolerance make shantung maple (Acer truncatum) and caddo sugar maple (A. saccharum) good candidates for midwestern landscapes. Improving cutting propagation or mound layering techniques could increase the availability of these species. The influence of time of year, cutting position, and auxin concentration, formulation, and solvent on rooting of stem cuttings of shantung maple was investigated. Semi-hardwood cuttings rooted best (55%). Generally, rooting percentage decreased as indole-3-butyric acid (IBA) concentration increased. Cutting position, auxin formulation, and solvent did not affect rooting. Mean root number and mean root length were unaffected by treatments. Results suggest semi-hardwood cuttings and low IBA concentrations [< 2500 ppm (0.25%)] promote rooting. Auxin concentration influenced rooting of caddo and shantung maple mound layered shoots. Rooting peaked at 15,000 ppm (1.5%) IBA for both caddo (71%) and shantung maples (34%). Mean root number for caddo, but not shantung, increased as IBA concentration increased. Differences in mean root length were not significant. Growers may now propagate caddo maple by mound layering. For shantung maple propagation, stem cuttings are recommended. Propagation substrates can strongly influence rooting success of stem cuttings. Eastern redcedar (Juniperus virginiana) chips (ERC) have been suggested as a propagation substrate component. This report investigated ERC as a perlite substitute in a 3 perlite: 1 sphagnum peat moss (v/v) rooting substrate. Stem cuttings of spreading euonymus (Euonymus kiautschovicus), forsythia (Forsythia x intermedia), English ivy (Hedera helix), lantana (Lantana camara), and coleus (Solenostemon scutellarioides) were rooted in substrates containing increasing concentrations of ERC hammer milled to pass a 4.8 mm (0.19 in) screen. All species rooted well (≥95%) in all substrates except forsythia which rooted poorly in all substrates (8% to 36%). ERC did not affect mean root number or mean root length in any species except spreading euonymus where mean root number peaked at 0% and 100% ERC content and mean root length decreased with increasing ERC content. Bulk density, container capacity, and total porosity increased as ERC replaced perlite. Physical properties of all substrates were suitable for cutting propagation. ERC can effectively replace perlite in rooting substrates for many ornamental species.
Keywords: Alternative substrates; Auxin; Indole-3-butyric acid; Perlite; Substrate physical properties; Vegetative propagation; Horticulture (0471)